Balance between paid and unpaid labour a study on female garment workers in Bangladesh - Ahmed, Md. Sultan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2024.